Association between iodine nutrition and cervical lymph node metastasis of papillary thyroid microcarcinoma - Zhao, Hengqiang; Hu, Jin; Cui, Le; Gong, Yiping; Huang, Tao (Frontiers in Endocrinology, 2023)
We aimed to investigate the association between iodine intake and nodal metastasis stratified by central lymph node metastasis (CLNM) and lateral lymph node metastasis (LLNM) of papillary thyroid microcarcinoma (PTMC). Urinary iodine concentration (UIC) and clinicopathological characteristics were used to identify factors associated with CLNM and LLNM using logistic regression analysis. A sum of 3858 PTMC patients were enrolled. The median UIC (MUI) of patients with CLNM or LLNM was not statistically different from those without nodal metastasis. Male patients had a higher MUI than females (183.4 μg/L vs 173.6 μg/L). Female patients with extracapsular extension had a higher MUI than those without it (210.0 μg/L vs 172.1 μg/L). Male patients with LLNM had a significantly lower MUI than those without LLNM (134.7 μg/L vs 187.9 μg/L). Female patients with more than adequate iodine intake were more likely to present with CLNM and extrathyroidal extension than those with adequate iodine intake with odds ratio (95% confidence interval) of 1.23 (1.01-1.51) and 1.59 (1.09-2.32) after adjustment. Iodine nutrition was not found to be associated with LLNM. In addition, patients with a younger age, larger tumors, extrathyroidal extension, and intrathyroidal spread were more likely to be CLNM, while nodular goiter presented with a protective factor; CLNM was the only factor associated with LLNM of PTMC in both genders. In conclusion, iodine nutrition has a much closer association with female than male patients, and high iodine intake may be associated with CLNM and extrathyroidal extension in female PTMC patients.